Understanding Russia : the challenges of transformation - Laruelle, Marlène, 1972- (Rowman & Littlefield, 2019)
This timely book provides a comprehensive overview of the geographical, historical, political, cultural, and geostrategic factors that drive Russia today. Explaining Russia's perspective, it offers a much-needed analysis that will help readers understand how the country deals with its domestic issues and how these influence Russian foreign policy.